Quality Of Service Of The Rehabilitation Section At The Palu City National Narcotic Board - Rachmat Agung; Frederikus Antonius Mana; Umiyati Haris; Syahrabudin Husein Enala; Muhammad Novan Prasetya (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
This research aims to find out the quality of the rehabilitation section services at the Palu City National Narcotics Agency Office. The type of research used is qualitative research. The determination of informants was carried out purposively. The types of data used are primary and interactive data from Miles and Huberman, namely data collection, data reduction, data presentation and drawing conclusions. The theory used is the theory of Parasuraman, Zeithaml and Berry in Pasolong (2007). The results of the research show that the quality of services of the Rehabilitation Section at the Palu City National Narcotics Agency Office cannot be said to be effective so that the output produced is not optimal and in accordance with the quality of public services. Despite the many obstacles and problems that occur when providing services to the community regarding the provision of services in the rehabilitation section at the Palu City National Narcotics Agency Office. There is a need to increase the provision of services to the community, especially in terms of rehabilitation services to people who abuse drugs, both in terms of mentoring and providing moral support to victims of drug abuse. Thus, the researchers draw the conclusion that the quality of the rehabilitation section services at the Palu City National Narcotics Agency Office is not optimal.